Genomic Insights on Variation Underlying Capsule Expression in Meningococcal Carriage Isolates From University Students, United States, 2015–2016 - Whaley, Melissa J.; Vuong, Jeni T.; Topaz, Nadav; Chang, How-Yi; Thomas, Jennifer Dolan; Jenkins, Laurel T.; Hu, Fang; Schmink, Susanna; Steward-Clark, Evelene; Mathis, Marsenia; Rodriguez-Rivera, Lorraine D.; Retchless, Adam C.; et al. (Frontiers in Microbiology, 2022)
In January and February 2015, Neisseria meningitidis serogroup B (NmB) outbreaks occurred at two universities in the United States and mass vaccination campaigns using MenB vaccines were initiated as part of a public health response. Meningococcal carriage evaluations were conducted concurrently with vaccination campaigns at these two universities and at a third university, where no NmB outbreak occurred. Meningococcal isolates (N = 1,514) obtained from these evaluations were characterized for capsule biosynthesis by whole genome sequencing. Functional capsule polysaccharide synthesis (cps) loci belonging to one of seven capsule genogroups (B, C, E, W, X, Y, and Z) were identified in 122 isolates (8.1%). Approximately half (732, 48.4%) of isolates could not be genogrouped due to the lack of any serogroup-specific genes. The remaining 660 isolates (43.5%) contained serogroup-specific genes for genogroup B, C, E, W, X, Y, or Z, but had mutations in the cps loci. Identified mutations included frameshift or point mutations resulting in premature stop codons, missing or fragmented genes, or disruptions due to insertion elements. Despite these mutations, 49/660 isolates expressed capsule as observed with slide agglutination, while 45/122 isolates with functional cps loci did not express capsule. Neither the variable capsule expression nor the genetic variation in the cps locus was limited to a certain clonal complex, except for capsule null isolates (predominantly clonal complex 198). Most of the meningococcal carriage isolates collected from student populations at three U.S. universities were nongroupable as a result of either being capsule null or containing mutations within the capsule locus. Several mutations inhibiting expression of the genes involved with the synthesis and transport of the capsule may be reversible, allowing the bacteria to switch between an encapsulated and nonencapsulated state. These findings are particularly important as carriage is an important component of the transmission cycle of the pathogen, and understanding the impact of genetic variations on the synthesis of capsule, a meningococcal vaccine target and an important virulence factor, may ultimately inform strategies for control and prevention of disease caused by this pathogen.